Scale dependence of biotic homogenisation by urbanisation: A comparison of urban bird communities between central argentina and northern Finland - Leveau, Lucas Matias; Jokimäki, Jukka; Kaisanlahti Jokimäki, Marja Liisa (European Journal of Ecology)
Recent studies showed contrasting results about the homogenising force of urbanisation on bird community composition at large and regional scales. We studied whether urbanisation promotes the homogenisation of wintering bird communities and if this varies when comparing towns located within a specific region and towns located in two different biomes of two countries. We used both similarity indices based on the presence/absence data and the abundance data in comparing communities. Processes governing bird community dissimilarity between urbanisation levels were examined with the partitioning of Sörensen index in species turnover and nestedness. We made bird surveys in town centres and suburban habitats of three cities located in the Pampean region of Argentina and in the boreal region of Finland using a single-visit study plot method. Rarefacted species richness did not differ amongst the town centres between the countries, but it was higher in the suburban areas of Argentina than in Finland. At the country-level comparison, we found a higher similarity amongst the town centres than amongst the suburban areas; whereas at the regional comparison, similarity between town centres was comparable to the similarity between suburban areas. The use of an abundance-based index produced a higher similarity between town centre communities of both countries than when using a presence-based index. The dissimilarity between habitats in Argentina was related to nestedness and to species turnover in Finland. Our results indicate that urban-based biotic homogenisation of bird communities is dependent on the scale used, being more evident when comparing cities of different biomes where the same and abundant bird species, such as sparrows and doves, dominate. At the regional scale, quite a high beta-diversity can still be found within urban habitats. Processes of community dissimilarity between urban habitats may differ according to the regional pool of species, being more related to nestedness toward the tropics. Fil: Leveau, ...